DWCS : a dynamic web cache selection algorithm - Zhang, Baili (2013)
The main aim of cache selection algorithms in current proxy servers is to get higher hit-ratio, they usually don't concern the validation and update of outdate pages. In this paper a new cache benefit model is defined, the relevant factors including validation cost and update cost are considered to obtain the optimal cache set. According to the cache model, an algorithm - DWCS (Dynamic Web Cache Selection) is presented, and it is proved to be optimal under the reasonable hypothesis. The experimental results show the efficiency of DWCS algorithm.